2021
DOI: 10.3390/polym13203532
|View full text |Cite
|
Sign up to set email alerts
|

Membranes for Cation Transport Based on Dendronized Poly(epichlorohydrin-co-ethylene oxide). Part 1: The Effect of Dendron Amount and Column Orientation on Copolymer Mobility

Abstract: Dendronized polyethers give rise to columnar LC structures which can successfully act as cation transport materials. Therefore, we prepared two different materials, based on Poly(epichlorohydrin-co-ethylene oxide) (PECH-co-EO) grafted with methyl 3,4,5-tris[4-(n-dodecan-1-yloxy)benzyloxy] benzoate, containing 20% or 40% modified units, respectively. The obtained polymers were characterized by differential scanning calorimetry (DSC), X-ray diffraction and optical microscopy between crossed polars (POM) and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…In Part 1 of this paper [25], we showed that grafting of Poly(epichlorohydrin-coethylene oxide) with Tap group, induced crystallization of the copolymer main chain, and that this effect was more evident in the copolymer-based oriented membranes. Crystallinity calculated from DSC data lay around 30% in the unoriented samples, whereas it increased to 38% in oriented CP20 and to 52% in oriented CP40.…”
Section: Morphological Characterization Wettability and Water Uptakementioning
confidence: 93%
See 3 more Smart Citations
“…In Part 1 of this paper [25], we showed that grafting of Poly(epichlorohydrin-coethylene oxide) with Tap group, induced crystallization of the copolymer main chain, and that this effect was more evident in the copolymer-based oriented membranes. Crystallinity calculated from DSC data lay around 30% in the unoriented samples, whereas it increased to 38% in oriented CP20 and to 52% in oriented CP40.…”
Section: Morphological Characterization Wettability and Water Uptakementioning
confidence: 93%
“…The chemical modification of P(ECH-co-EO) was performed as described in Part 1 [25]. In the present paper, we focused our attention on the polymer modified at 20% and 40%, which are labelled as CP20 and CP40.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the membranes prepared with dendronized poly (epichloroydrin-co-ethylene oxide), which present 20% and 40% of grafted tap dendrons, have been intensely studied in Part 1 and 2 of [ 31 , 32 ]. In these studies, PECH-co-EO units were chemically modified with 20% (CP20) and 40% (CP40) of tap dendrons.…”
Section: Introductionmentioning
confidence: 99%